THE IMPLEMENTATION OF PATIENT SAFETY GOALS FOR PATIENTS' SATISFACTION IN THE HEMODIALYSIS UNIT - Ambarwati, Dwi; Dewi, Arlina (Universitas Airlangga, 2024)
Background: Surveys on patient safety in dialysis units uncover a range of significant patient safety issues. Hemodialysis centers are particularly vulnerable to adverse events due to a number of risk factors, such as machine malfunctions, excessive blood loss, patient falls, prescription errors, and inadequate infection control procedures. Aim: Analyze the problem of implementing patient safety goals and describe the patients' satisfaction with the implementation of patient safety goals. Methods: This study employs a concurrent embedded methodology with a mixed-methods design, utilizing quantitative data to complement the qualitative data. Applying the focus group discussion (FGD) technique, questionnaires and observations of hemodialysis patients' satisfaction with implementing patient safety goals were utilized to complete the data collection. Results: According to the patient satisfaction survey, two patients were worried that their dialyzer tubes had been mixed up, earning a negative score of 5.13%. 23.07% of patients had negative results on the infection prevention risk questionnaire; 3 patients (7.69%) only seldom cleaned their hands before starting dialysis, and 6 patients (15.38%) did not. Conclusion: The implementation of patients' identification and the reduction of infection risk through hand hygiene have not been carried out consistently, concerning patient safety goals in the hemodialysis unit. Keywords: hand hygiene, hemodialysis, patient safety goals, patients' satisfaction, patients' identification